High‐Capacity Spherical LiNi0.82Co0.15Al0.03O2 Cathode for Lithium‐Ion Batteries. Issue 31 (16th August 2019) - Bai, Guoliang; Wang, Chunhua; Luo, Jiaojiao; Xia, Hongyu; Luo, Qibo; Wang, Junwei; Cheng, Di
Abstract: A novel high‐capacity‐spherical LiNi0.82 Co0.15 Al0.03 O2 (NCA) cathode material is prepared by two‐step method. Firstly, the co‐precipitation method is used to prepare Ni0.82 Co0.15 Al0.03 (OH)2 precursors. Then, the sol‐gel method is applied to mix the Ni0.82 Co0.15 Al0.03 (OH)2 precursors and Li2 CO3 so that Li can get in touch with Ni0.82 Co0.15 Al0.03 (OH)2 precursors evenly. Compared to the conventional Ni‐rich cathode materials, the NCA cathode material exhibits improved reversible capacity, capacity retention, rate performance and better thermal stability. But beyond that, improving the thermal stability of the NCA cathode material at 4.5 V is also very important. Even more remarkably, the NCA cathode material exhibits an excellent rate capacity of about 175 mAh g −1 at 5 C with a cut‐off potential range between 2.8 and 4.5 V, corresponding to around 670 Wh kg −1 at 25 °C. It also provides significantly improved thermal stability at the high temperature of 60 °C, with a discharge capacity of 125.1 mAh g −1 after 200 cycles with capacity retention of 56.3%. Therefore, the NCA cathode material is one of the best classes of cathode materials that could satisfy the demands of future electric vehicles. Abstract : A novel high‐capacity‐spherical LiNi0.82 Co0.15 Al0.03 O2 (NCA) cathode material was prepared by two‐step method. Compared to the conventional Ni‐rich cathode materials, the NCA cathode material exhibited higher reversible capacity, capacity retention and better thermal stability.